A RAPID FUSION METHOD FOR SEPARATION OF BERYLLIUM-10 FROM SOILS AND SILICATES - INFERENCES FROM 10BE - Stone J. (My University, 1998)
Beryllium for isotopic analysis by accelerator mass spectrometry (AMS) can be extracted efficiently from geological materials using a procedure based on fusion with a mixture of KHF2 and Na2SO4. In the presence of this flux, Be forms the fluoroberyllate anion (BeF42-), freely extractable into hot water, whereas Fe, Al, and Ti form highly insoluble fluorides. Beryllium precipitated as hydroxide after removal of K and F from the leachate is accompanied by only microgram quantities of Fe, Al, and Ti. Isotopic equilibrium is attained during the fusion, making the method suitable for AMS preparations in which 9Be carrier is added to 10Be-bearing sample material. The Be extraction efficiency is typically 70-90% for soils, beryl, and island-arc basalt samples, compared to ~10-3 to 10-5 for Ti, Fe, and Al. The combination of Be extraction and purification into a single fusion/leaching procedure makes the technique very efficient. A batch of samples can be processed in one extended day or two short days.